Impact study of integrated nutrition package and holistic fertility management in dairy buffalo in Nepal - Singh, T. (International Livestock Research Institute, 2023)
CGIAR’s Research Initiative on Sustainable Animal Productivity (also known as SAPLING – sustainable animal productivity for livelihoods, income, nutrition, and gender inclusion) has adopted an integrated approach to contribute to the transformation of the dairy sector in Nepal to make dairy production with buffaloes more productive, resilient, equitable and sustainable. With partners, researchers are developing a dairy genetic gains platform, a feed advisory platform, improving reproductive health and access to integrated delivery of genetics, feed and health services and formal institutional arrangements for the co-creation of solutions.